The Potential Role of Phytonutrients Flavonoids Influencing Gut Microbiota in the Prophylaxis and Treatment of Inflammatory Bowel Disease - Wang, Lina; Gao, Mengxue; Kang, Guangbo; Huang, He (Frontiers in Nutrition, 2021)
Inflammatory bowel disease (IBD), characterized by the chronic inflammation of the gastrointestinal tract, is comprised of two idiopathic chronic intestinal inflammatory diseases. As the incidence of IBD increases, so does the need for safe and effective treatments. Trillions of microorganisms are colonized in the mammalian intestine, coevolved with the host in a symbiotic relationship. Gut microbiota has been reported to be involved in the pathophysiology of IBD. In this regard, phytonutrients flavonoids have received increasing attention for their anti-oxidant and anti-inflammatory activities. In this review, we address recent advances in the interactions among flavonoids, gut microbiota and IBD. Moreover, their possible potential mechanisms of action in IBD have been discussed. We conclude that there is a complex interaction between flavonoids and gut microbiota. It is expected that flavonoids can change or reshape the gut microbiota to provide important considerations for developing treatments for IBD.